A method for manufacturing an all solid state battery and an all solid type batterythereby

KR103013600B1Active Publication Date: 2026-09-01LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020250014051
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-02-04
Publication Date
2026-09-01
Estimated Expiration
2038-10-26

Smart Images

  • Figure 112025012705411-PAT00001_ABST
    Figure 112025012705411-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing an all-solid-state battery and an all-solid-state battery manufactured by said method, wherein the all-solid-state battery comprises an inorganic electrolyte as the electrolyte and the method does not require excessively high pressure or temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing an all-solid-state battery and an all-solid-state battery manufactured by said method, wherein the all-solid-state battery comprises an inorganic electrolyte as the electrolyte and the method does not require excessively high pressure or temperature. Background Technology

[0003] Lithium-ion batteries using liquid electrolytes have a structure in which the negative and positive electrodes are separated by a separator; however, if the separator is damaged due to deformation or external impact, a short circuit may occur, which can lead to risks such as ignition or explosion. Therefore, the development of solid electrolytes capable of ensuring safety in the field of lithium-ion secondary batteries is a critical task.

[0004] Lithium-ion batteries utilizing solid electrolytes offer enhanced safety, improved reliability by preventing electrolyte leakage, and the advantage of facilitating the fabrication of thin-walled batteries. Furthermore, the ability to use lithium metal as the negative electrode improves energy density; consequently, they are gaining attention as next-generation batteries, with promising applications in high-capacity batteries for electric vehicles as well as small rechargeable batteries.

[0005] However, lithium secondary batteries using solid electrolytes exhibit lower ionic conductivity compared to liquid electrolytes, and their output characteristics deteriorate, particularly at low temperatures. Furthermore, the solid electrolyte layer has poorer adhesion to the electrode compared to liquid electrolytes, leading to increased interfacial resistance between the electrode and the solid electrolyte layer. To address this issue, applying excessively high pressure during the bonding of the electrode and the solid electrolyte layer can cause degradation of the battery device, such as the breakage of electrode active material particles. For these reasons, batteries using solid electrolytes do not achieve the same full capacity as batteries using liquid electrolytes, resulting in capacities lower than their design or theoretical levels. Therefore, the development of new all-solid-state batteries with improved adhesion between the electrode and the solid electrolyte layer is required. The problem to be solved

[0007] The present invention aims to provide an all-solid-state battery that improves the conductivity of lithium ions by increasing the adhesion and contact area between the electrode and the solid electrolyte layer to resolve the aforementioned problems, thereby enhancing the electrode capacity and output characteristics. Furthermore, another objective of the present invention is to provide a method for manufacturing an all-solid-state battery having such improved battery characteristics. Meanwhile, other objectives and advantages of the present invention will be understood from the following description. Additionally, it will be readily apparent that the objectives and advantages of the present invention can be realized by the means or methods described in the claims and combinations thereof. means of solving the problem

[0009] The first aspect of the present invention relates to a method for manufacturing an electrode assembly for an all-solid-state battery, wherein the method comprises interposing a positive electrode, a negative electrode, and a solid electrolyte layer between the positive electrode and the negative electrode, wherein the positive electrode, the solid electrolyte layer, and the negative electrode are each sequentially stacked in a non-pressurized state to form a stacked structure, and subsequently, a lamination process is performed to bond electrode elements by applying heat and / or pressure to the stacked structure.

[0010] A second aspect of the present invention is that, in the first aspect, the pressurizing step is performed under conditions of a pressure of 80 MPa to 120 MPa and a temperature of 100°C to 150°C.

[0011] A third aspect of the present invention is that, in the first aspect, the pressurization step is performed under a pressure of 350 MPa to 450 MPa and room temperature conditions.

[0012] A fourth aspect of the present invention relates to a method for manufacturing an electrode assembly for an all-solid-state battery, wherein, in at least one of the aforementioned aspects, the method comprises: S10) preparing an anode slurry and a cathode slurry; S20) applying the slurries to an anode current collector and a cathode current collector, respectively, and drying them to prepare a preliminary electrode; S30) preparing a slurry for an all-solid-state electrolyte layer, applying it to a release liner, and drying it to prepare a preliminary solid electrolyte layer; and S40) stacking the preliminary electrodes and the preliminary solid electrolyte layer and then pressurizing them to manufacture an electrode assembly; wherein the anode, cathode, and solid electrolyte layer comprise a sulfide-based solid electrolyte, and the preliminary electrode and the preliminary solid electrolyte layer are maintained in a state not pressurized until step S40) is performed.

[0013] A fifth aspect of the present invention is that, in the fourth aspect, step S40) is performed under conditions of a pressure of 80 MPa to 120 MPa and a temperature of 100°C to 150°C or under conditions of a pressure of 350 MPa to 450 MPa and room temperature.

[0014] A sixth aspect of the present invention relates to a method for manufacturing an electrode assembly for an all-solid-state battery, wherein, in at least one of the aforementioned aspects, the method comprises: S210) preparing a positive electrode and a negative electrode slurry; S220) applying the electrode slurries to a positive electrode current collector and a negative electrode current collector, respectively, and drying them to prepare an unpressurized preliminary electrode; S230) preparing a slurry for an all-solid-state electrolyte layer and applying it to a preliminary positive electrode surface or a preliminary negative electrode surface and drying it; and S240) stacking the unpressurized electrodes corresponding to the result of step S230) such that a solid electrolyte layer is disposed between them and pressurizing them to manufacture an electrode assembly, wherein the positive electrode, the negative electrode, and the solid electrolyte layer comprise a sulfide-based solid electrolyte.

[0015] The seventh aspect of the present invention is that, in the sixth aspect, the step S240) is performed under conditions of a pressure of 80 MPa to 120 MPa and a temperature of 100°C to 150°C or under conditions of a pressure of 350 MPa to 450 MPa and room temperature.

[0016] The eighth aspect of the present invention is that, in at least one of the aforementioned aspects, the electrode comprises an electrode active material and a solid electrolyte, and the solid electrolyte comprises a sulfide-based solid electrolyte.

[0017] A ninth aspect of the present invention is that, in at least one of the aforementioned aspects, the solid electrolyte layer comprises a sulfide-based solid electrolyte.

[0018] The tenth aspect of the present invention is that, in at least one of the aforementioned aspects, the solid electrolyte layer further comprises a binder resin.

[0019] In addition, the present invention relates to an electrode assembly for an all-solid-state battery that is manufactured by a manufacturing method according to at least one of the aforementioned aspects. Effects of the invention

[0021] The battery manufacturing method according to the present invention allows lamination to proceed under conditions that are not harsh in terms of temperature or pressure, thereby reducing defects such as detachment or breakage of electrode active material particles during the process. Additionally, bending and elongation of the electrode, electrolyte layer, and unit cell are reduced. Furthermore, battery performance is improved, such as low interfacial resistance and improved ion conductivity, as the electrode active material layer and the solid electrolyte layer are in close contact. Brief explanation of the drawing

[0023] The drawings attached to this specification illustrate preferred embodiments of the present invention and serve to help to better understand the technical concept of the present invention together with the description of the invention above; therefore, the present invention is not to be interpreted as being limited only to the matters described in such drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings included in this specification may be exaggerated to emphasize a clearer explanation. FIGS. 1 and FIGS. 2 are process flow diagrams illustrating a method for manufacturing an electrode assembly according to the present invention in the order of process steps. Figure 3 is an SEM image showing a cross-section of the electrolyte membrane of the battery according to Example 1. Figure 4 is an SEM image showing a cross-section of the electrolyte membrane of the battery according to Example 2. Figure 5 is an SEM image showing a cross-section of the electrolyte membrane of the battery according to Example 3. Figure 6 is an SEM image showing a cross-section of the electrolyte membrane of the battery according to Example 4. Figure 7 is an SEM image showing a cross-section of the electrolyte membrane of a battery according to Comparative Example 1. Figure 8 is an SEM image showing a cross-section of the electrolyte membrane of a battery according to Comparative Example 2. Figure 9 is an SEM image showing a cross-section of the electrolyte membrane of a battery according to Comparative Example 4. Figure 10 shows a comparison of the ion conductivity of batteries according to Example 1, Example 2, Comparative Example 1, and Comparative Example 2. Figure 11 shows a comparison of the initial charge-discharge curves of Example 2 and Comparative Example 2. Specific details for implementing the invention

[0024] Embodiments of the present invention will be described in detail below. Prior to this, terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings. Instead, based on the principle that the inventor can appropriately define the concepts of terms to best describe their invention, they should be interpreted in a meaning and concept consistent with the technical spirit of the present invention. Therefore, the configurations described in the embodiments of this specification are merely one preferred embodiment of the present invention and do not represent all aspects of the technical spirit of the present invention. It should be understood that various equivalents and modifications capable of replacing them may exist at the time of filing this application.

[0026] Throughout this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0028] Additionally, terms such as “about,” “substantially,” as used throughout this specification, are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the stated meaning, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosure in which precise or absolute values ​​are mentioned to aid in understanding this invention.

[0030] Throughout this specification, the description “A and / or B” means “A or B or both.”

[0032] The present invention relates to a method for manufacturing a lithium-ion secondary battery and a battery manufactured by said method. In the present invention, the lithium-ion secondary battery is an all-solid-state battery that uses a solid electrolyte as the electrolyte.

[0033] In the present invention, the all-solid-state battery comprises a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, wherein the solid electrolyte layer comprises a sulfide-based solid electrolyte. Furthermore, in one embodiment of the present invention, the positive electrode and the negative electrode each independently comprise an electrode active material and a solid electrolyte, wherein the solid electrolyte may comprise a sulfide-based solid electrolyte.

[0034] Typically, all-solid-state batteries are manufactured by a method (lamination) in which a positive electrode, a negative electrode, and a solid electrolyte layer are prepared, stacked sequentially, and then pressurized under high temperature conditions to bond the layers together. However, in the manufacturing of conventional all-solid-state batteries, the lamination process is performed by applying heat and / or pressure after each layer has been dried and / or compressed. Therefore, in order for sufficient bonding between layers to occur, high pressure must be applied or the process must be performed under high temperature conditions, and this process causes degradation of the electrode active material.

[0035] Accordingly, the present invention provides a method for manufacturing a battery that prevents the degradation of electrodes while ensuring sufficient adhesion between stacked battery elements. The battery manufacturing method according to the present invention prepares a stacked structure in which a positive electrode, a solid electrolyte layer, and a negative electrode are sequentially stacked, and forms an electrode assembly by laminating the stacked structure under a predetermined temperature and pressure conditions to achieve interlayer bonding, wherein the positive electrode, the solid electrolyte layer, and the negative electrode are maintained in an unpressurized state until the stacked structure is pressurized.

[0036] In this specification, the term 'lamination' refers to a process of bonding the components of a laminated structure by adhering them to each other, and said process is performed under predetermined pressure and / or temperature conditions. The pressure may be applied using various pressure members, such as various pressure rollers or pressure jigs. The term 'unpressurized state' refers to a state in which the structural features of the solidified dry state, such as thickness, size, planarity, porosity, etc., are maintained after the solvent has been removed following the application of each slurry, and no artificial pressure by a pressure member is applied to the laminated structure until the lamination process.

[0037] In one embodiment of the present invention, the lamination process may be performed under pressure conditions ranging from 80 MPa to 120 MPa. Additionally, when performing the lamination process, the laminated structure may be heated to a temperature ranging from about 100°C to 150°C. Under the above pressure and temperature conditions, the adhesion between each layer can be induced to a sufficient level without causing problems such as stretching, breakage, or detachment of the electrode or electrolyte layer.

[0038] Meanwhile, the above lamination process may be performed under room temperature conditions. When performed under room temperature conditions, it is preferable that the applied pressure be controlled within the range of 350 MPa to 450 MPa. In the present invention, the room temperature condition may be in the range of 20℃ to 30℃.

[0039] The method for manufacturing an all-solid-state battery according to the present invention can be implemented in any one of the following various embodiments.

[0040] FIGS. 1 and 2 illustrate the battery manufacturing method of the present invention in a schematic manner according to the process sequence.

[0042] FIG. 1 illustrates a method for manufacturing a battery according to a first embodiment of the present invention. With reference thereto, the method for manufacturing a battery has been described in more detail.

[0044] First, an anode slurry and a cathode slurry are prepared (S10). Each slurry contains an electrode active material and a solid electrolyte, and the solid electrolyte may include a sulfide-based solid electrolyte. These components are introduced and dispersed in a suitable solvent to prepare a slurry for forming electrodes. The solvent is not particularly limited, but may include a nonpolar solvent having no or very small intramolecular dipole moment that has low reactivity with the sulfide-based solid electrolyte. In one embodiment of the present invention, the solvent polarity index (Snyer Polarity Index) may be 3 or less or the relative polarity may be 0.2 or less. For example, as an aromatic solvent, benzene, toluene, xylene, methoxybenzene, as a chain-type aliphatic solvent, hexane, heptane, octane, nonane, decane, and as a cyclic aliphatic solvent, cycloheptane, etc., can be used as a polyhydrocarbon solvent. In addition, each electrode slurry may include one or more selected from a conductive material and a binder resin. The electrode slurry may further include additives such as an antioxidant or a reducing agent as needed.

[0045] The volume ratio of the active material and solid electrolyte constituting the electrode may be 70-80% for the active material and 30-20% for the solid electrolyte. As for the weight ratio of the negative electrode, depending on the size of the active material, the active material may be 60-80% and the solid electrolyte 20-40%. For the positive electrode, the active material may be 60-95% and the solid electrolyte 5-40%. In addition, a small amount of conductive material and binder may be added in a range of about 10% or less by weight ratio relative to the electrode active material layer. In one embodiment of the present invention, although not limited thereto, a composite of the electrode active material and the solid electrolyte may be formed in advance to effectively secure the contact area between the active material and the solid electrolyte. Meanwhile, in one embodiment of the present invention, the content of the solid component excluding the solvent in the slurry may be appropriately controlled within 50 wt% to 80 wt%.

[0047] Next, each of the above slurries is applied to a positive current collector and a negative current collector, respectively, and dried to prepare a preliminary electrode (S20). Appropriate application methods, such as slot die coating or a doctor blade, may be used for applying the slurry. The drying may be performed by selecting an appropriate method from various options, such as natural drying, hot air drying, cold air drying, blowing air drying, or heating drying, but is not limited to a specific method; any method that allows the solvent in the slurry to be removed to obtain a solidified preliminary electrode may be used. As described above, the preliminary electrodes are maintained in an unpressurized state after drying and before the lamination process is performed on the laminated structure described later.

[0048] Next, a slurry for a solid electrolyte layer is prepared. The slurry may include a sulfide-based solid electrolyte as the solid electrolyte material, and the slurry is prepared by adding and dispersing the solid electrolyte in a suitable solvent. The solvent is not particularly limited, but may include nonpolar solvents with no or very small intramolecular dipole moments that have low reactivity with sulfide-based solid electrolytes, such as aromatic or aliphatic solvents. Regarding the solvent for the solid electrolyte layer slurry, one may refer to the description of the solvent used for the electrode forming slurry mentioned above, and a detailed description is omitted to avoid repetition. Additionally, the slurry may further include a binder resin or, if necessary, additives such as an antioxidant or a reducing agent.

[0049] In this way, when the slurry for the solid electrolyte layer is prepared, it is divided, and a portion is applied to the surface of a preliminary anode and dried to manufacture an anode member (S130). The remainder of the slurry for the solid electrolyte layer is applied to the surface of a preliminary cathode and dried to manufacture a cathode member (S140). Either the manufacturing of the anode member or the manufacturing of the cathode member may be performed first, or they may be manufactured simultaneously.

[0050] The above slurry may be applied using an appropriate application method, such as slot die coating or a doctor blade. The above drying may be performed by selecting an appropriate method among various methods such as natural drying, hot air drying, cold air drying, blowing air drying, or heating drying, but is not limited to a specific method; any method capable of removing the solvent from the slurry to obtain a solidified pre-solid electrolyte layer may be used. As described above, the solid electrolyte layer is maintained in an unpressurized state after drying and before the lamination process for the laminated structure described later is performed.

[0051] Next, the anode member and the cathode member are laminated so that their slurry coating surfaces are in contact to prepare a laminated structure, and a lamination process is performed to bond the coating surfaces to each other, thereby obtaining an electrode assembly (S150). At this time, the lamination process is performed under conditions of a pressure of 80 MPa to 120 MPa and a temperature of 100°C to 150°C. Meanwhile, the lamination process may be performed under room temperature conditions. When performed under room temperature conditions, it is preferable that the applied pressure be controlled within the range of 350 MPa to 450 MPa.

[0052] In addition, in one embodiment of the present invention, the lamination process may be performed for about 30 seconds to 600 seconds. However, the pressurization time may be controlled to an appropriate range within the above range depending on the thickness of the electrode assembly, the applied pressure, and the temperature conditions.

[0054] FIG. 2 illustrates a method for manufacturing a battery according to a second embodiment of the present invention, wherein a solid electrolyte layer is formed on the surface of either a positive electrode or a negative electrode, and then the two are joined to form an electrode assembly. Preferably, the solid electrolyte layer is formed on the surface of the negative electrode. Next, the method for manufacturing a battery according to the present invention will be described in more detail with reference to FIG. 2.

[0055] First, an anode slurry and a cathode slurry are prepared (S210), and each of the slurries is applied to an anode current collector and a cathode current collector, respectively, and dried to prepare a preliminary electrode (S220). For a description of each step, refer to the first embodiment described above, and a detailed description is omitted to avoid duplication of description. As described above, the preliminary electrodes are kept in an unpressurized state after drying and before the lamination process for the laminated structure described later is performed.

[0056] Next, a slurry for a solid electrolyte layer is prepared. Since the preparation of the slurry can be referenced from the first embodiment described above, a detailed description is omitted to avoid duplication. Once the slurry for the solid electrolyte layer is prepared, it is applied to the surface of a first electrode, which is either a preliminary anode or a preliminary cathode, and dried to manufacture an electrode member in which a preliminary solid electrolyte layer is formed on the surface of the preliminary electrode (S230). Next, the electrode member and the second electrode, which is the remaining electrode, are laminated to prepare a laminated structure, and a lamination process is performed to bond the second electrode and the solid electrolyte layer to each other, thereby obtaining an electrode assembly (S240). Here, if the first electrode is a positive electrode, the second electrode is a negative electrode, and conversely, if the first electrode is a negative electrode, the second electrode is a positive electrode. In one embodiment of the present invention, it is preferable that the first electrode is a negative electrode.

[0057] In the second embodiment above, as in the first embodiment, the electrode member and the remaining electrode are kept unpressurized until the lamination step is performed. Additionally, the lamination step is performed under conditions of a pressure of 80 MPa to 120 MPa and a temperature of 100°C to 150°C. Alternatively, the lamination process may be performed at room temperature, whereby the pressure may be controlled to a range of 350 MPa to 450 MPa.

[0059] In addition, the present invention relates to an all-solid-state battery comprising an electrode assembly manufactured by the above method, comprising a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode.

[0061] In the present invention, the electrode comprises a plurality of electrode active material particles and a solid electrolyte, wherein the solid electrolyte comprises a sulfide-based solid electrolyte. Additionally, the electrode may further comprise one or more of a conductive material and a binder resin as needed. Furthermore, the electrode may further comprise various additives for the purpose of supplementing or improving the physicochemical properties of the electrode. Meanwhile, in one embodiment of the present invention, the solid electrolyte may further comprise one or more of an oxide-based solid electrolyte and a polymer-based solid electrolyte.

[0063] In the present invention, when the electrode is a negative electrode, any material capable of being used as a negative electrode active material for a lithium-ion secondary battery may be used as the electrode active material. For example, the negative electrode active material may be carbon such as non-graphitizable carbon, graphite-based carbon, etc.; Li x Fe2O3(0≤x≤1), Li x WO2(0≤x≤1), Sn x Me 1-x Me y O z(Me:Mn,Fe,Pb,Ge;Me': Al, B, P, Si, Group 1, 2, and 3 elements of the periodic table, halogens; 0 <x≤1; 1≤y≤3; 1≤z≤8) 등의 금속 복합 산화물; 리튬 금속; 리튬 합금; 규소계 합금; 주석계 합금; SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4및 Bi2O5등의 금속 산화물; 폴리아세틸렌 등의 도전성 고분자; Li-Co-Ni 계 재료; 티타늄 산화물; 리튬 티타늄 산화물 등에서 선택된 1종 또는 2종 이상을 사용할 수 있다. 구체적인 일 실시양태에 있어서 상기 음극 활물질은 탄소계 물질 및 / 또는 Si을 포함할 수 있다.

[0065] When the above electrode is a positive electrode, the above electrode active material may be used without limitation as long as it is suitable for use as a positive electrode active material for a lithium-ion secondary battery. For example, the above positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; chemical formula Li 1+x Mn 2-x Lithium manganese oxides such as O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, LiMnO2, etc.; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, Cu2V2O7, etc.; chemical formula LiNi 1-x M x Ni-site type lithium nickel oxide represented by O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B, or Ga, and x = 0.01 ~ 0.3); chemical formula LiMn 2-x M xLithium manganese composite oxide represented by O2 (where M = Co, Ni, Fe, Cr, Zn, or Ta, and x = 0.01 ~ 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu, or Zn); LiNi x Mn 2-x It may include a spinel-structured lithium manganese complex oxide represented by O4; LiMn2O4 in which part of the Li in the chemical formula is substituted with alkaline earth metal ions; disulfide compounds; Fe2(MoO4)3, etc. However, it is not limited to these.

[0067] In one embodiment of the present invention, the positive and / or negative active material may have a particle size of about 0.01 μm to 50 μm and may have the form of a secondary particle formed by aggregating a plurality of particles.

[0069] In the present invention, the current collector may be a metal plate or the like that exhibits electrical conductivity, and may be appropriate according to the polarity of the current collector electrode known in the field of secondary batteries. In addition, the thickness of the current collector may be appropriately adjusted within a range of approximately 1 μm to 50 μm.

[0071] In the present invention, the conductive material is typically added in an amount of 1 to 30 weight percent based on the total weight of the mixture containing the electrode active material. Such conductive material is not particularly limited as long as it is conductive without causing chemical changes in the battery, and may include, for example, graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fiber or metal fiber; metal powders such as carbon fluoride, aluminum, or nickel powder; conductive whiskey such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or a mixture of two or more types of conductive materials such as polyphenylene derivatives.

[0073] In the present invention, the binder resin is not particularly limited as long as it is a component that assists in the bonding of the active material and the conductive material, and the bonding to the current collector, and examples include polyvinylidene fluoride, polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, and various copolymers. The binder resin may typically be included in a range of 1 to 30 weight% or 1 to 10 weight% relative to 100 weight% of the electrode layer.

[0075] Meanwhile, in the present invention, the electrode active material layer may include one or more additives such as an oxidation stabilizing additive, a reduction stabilizing additive, a flame retardant, a heat stabilizer, and an antifogging agent as needed.

[0077] In the present invention, the solid electrolyte membrane is interposed between the cathode and the anode and serves to electrically insulate the cathode and the anode while allowing lithium ions to pass through. The solid electrolyte membrane comprises a sulfide-based solid electrolyte. Additionally, if necessary, it may further comprise one or more selected from oxide-based solid electrolytes and polymer-based solid electrolytes. Furthermore, the solid electrolyte layer may further comprise a binder resin if necessary.

[0079] In the present invention, it is preferable that the sulfide-based solid electrolyte contains sulfur (S), has the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and also has electronic insulation properties. For example, a lithium ion-conducting inorganic solid electrolyte satisfying the composition represented by the following formula (1) may be provided.

[0081] Equation (1) L a1 M b1 P c1 Sd1 A e1

[0083] In Equation (1), L represents an element selected from Li, Na, and K, with Li being preferred. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge. Among these, B, Sn, Si, Al, and Ge are preferred, and Sn, Al, and Ge are more preferred. A represents I, Br, Cl, and F, with I and Br being preferred, and I being particularly preferred. a1 to e1 represent the compositional ratio of each element, and a1:b1:c1:d1:e1 satisfies 1 to 12:0 to 1:1:2 to 12:0 to 5. a1 is also preferred to be 1 to 9, and 1.5 to 4 is more preferred. b1 is preferred to be 0 to 0.5. d1 is also preferred to be 3 to 7, and 3.25 to 4.5 is more preferred. e1 is also preferred to be 0 to 3, and 0 to 1 is more preferred.

[0084] In the above formula (1), the composition ratio of L, M, P, S, and A is preferably such that b1 and e1 are 0, more preferably b1=0 and e1=0, and the ratio of a1, c1, and d1 (a1:c1:d1) is a1:c1:d1=1~9:1:3~7, and also preferably b1=0 and e1=0, and a1:c1:d1=1.5~4:1:3.25~4.5. The composition ratio of each element can be controlled by adjusting the amount of raw material compounds when manufacturing a sulfide-based solid electrolyte as follows.

[0086] Sulfide-based solid electrolytes can be amorphous (glassy) or crystallized (glassy ceramic), or only a portion of the whole may be crystallized.

[0087] In Li-PS-based glass and Li-PS-based glass ceramics, the ratio of Li2S to P2S5 is preferably 65:35 to 85:15 as a molar ratio of Li2S to P2S5, and more preferably 68:32 to 75:25. By setting the ratio of Li2S to P2S within this range, lithium ion conductivity can be improved. Specifically, the lithium ion conductivity is preferably 1×10⁻⁶ -4 S / cm or more, more preferably 1×10 -3 It can be greater than S / cm. There is no specific upper limit, but 1×10 -1 S / cm or less is the actual value.

[0088] Specific examples of compounds include those formed using a raw material composition containing Li2S and elemental sulfides of Groups 13 to 15. Specifically,

[0089] Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li 10 GeP2S 12Examples include Li2S-P2S5, Li2S-GeS2-Ga2S3, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li2S-Li3PO4-P2S5, Li2S-GeS2-P2S5, Li 10 GeP2S 12 A crystalline and / or amorphous raw material composition composed of [the above] is desirable because it has high lithium ion conductivity. An example of a method for synthesizing a sulfide solid electrolyte material using such a raw material composition is the amorphization method. Examples of amorphization methods include mechanical milling and melt quenching, among which mechanical milling is preferred. This is because processing at room temperature is possible, thereby simplifying the manufacturing process.

[0091] In addition, the present invention provides a battery module including the secondary battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.

[0093] Specific examples of the above-mentioned device include, but are not limited to, power tools that are powered by an electric motor; electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV); electric two-wheeled vehicles including electric bicycles (E-bike) and electric scooters (E-scooter); electric golf carts; and power storage systems.

[0095] The present invention will be described in more detail below through examples, but the following examples are intended to illustrate the invention and the scope of the invention is not limited thereto.

[0097] Examples

[0098] Example 1

[0099] Graphite and NMC (LiNi) as active materials for the manufacture of cathode and anode slurries 0.7 Mn 0.15 Co 0.15 O2 particles were used. Li2S-P2S5-LiCl (Mitsui metal) was used as the sulfide-based solid electrolyte. The cathode consisted of a mixture of graphite and solid electrolyte particles in a weight ratio of 80:20, and the anode consisted of a mixture of NMC and solid electrolyte particles in a weight ratio of 75:25. The experiment was conducted using a glove box filled with argon gas to avoid contamination from contact with air and moisture. A separate conductive material (Vapor Grown Carbon Fiber (VGCF)) and a binder (polyacrylate (SX-A334, Zeon)) were additionally added to the xylene solvent, and a slurry was prepared by rotating a paste mixer at 1,000 rpm for 5 minutes.

[0100] Next, each of the above slurries was applied to the positive current collector and the negative current collector, respectively, and dried to prepare a preliminary electrode.

[0101] The cathode and anode slurries were coated onto Cu and Al foils, respectively, using the doctor blade method, and dried at 60°C for more than 12 hours using a vacuum. A 10 µm thick Cu foil and a 12 µm thick Al foil were used as the cathode and anode current collectors, respectively.

[0102] Next, a slurry for the solid electrolyte layer was prepared.

[0103] A slurry for a solid electrolyte layer was prepared by mixing solid electrolyte particles (Cl-added Li2S-P2S5 (Mitsui metal)) and a binder (polyacrylate (SX-A334, Zeon)) in a xylene solvent inside an argon-filled glove box. At this time, the weight ratio of the solid electrolyte to the binder was 98:1. The slurry was prepared by stirring four times for 3 minutes using a paste mixer.

[0104] Afterwards, the slurry for the solid electrolyte layer was divided into two parts, with a portion applied to the surface of the cathode and the remainder applied to the surface of the anode and dried.

[0105] A slurry for a solid electrolyte layer prepared using the doctor blade method was applied to the surfaces of the cathode and anode prepared by applying and drying previously, and dried at 60°C for more than 12 hours using a vacuum.

[0106] Next, a laminated structure was prepared by stacking the coated surfaces facing each other, and then a lamination process was performed to bond the layers. At this time, the lamination process was performed at room temperature under a pressure of 400 MPa for about 10 minutes. The thickness of the solid electrolyte layer in the obtained electrode assembly was about 50 μm.

[0108] Example 2

[0109] The lamination process was performed in the same manner as in Example 1, except that the lamination process was carried out at approximately 120°C at a pressure of 100 MPa. The thickness of the solid electrolyte layer in the obtained electrode assembly was approximately 50 μm.

[0111] Example 3

[0112] A positive electrode slurry and a negative electrode slurry were prepared.

[0113] Graphite and NMC (LiNi) as active materials for the manufacture of cathode and anode slurries 0.7 Mn 0.15 Co 0.15O2 particles were used. Li2S-P2S5-LiCl (Mitsui metal) was used as the sulfide-based solid electrolyte. The cathode consisted of a mixture of graphite and solid electrolyte particles in a weight ratio of 80:20, and the anode consisted of a mixture of NMC and solid electrolyte particles in a weight ratio of 75:25. The experiment was conducted using a glove box filled with argon gas to avoid contamination from contact with air and moisture. A separate conductive material (Vapor Grown Carbon Fiber (VGCF)) and a binder (polyacrylate (SX-A334, Zeon)) were additionally added to the xylene solvent, and a slurry was prepared by rotating a paste mixer at 1,000 rpm for 5 minutes.

[0114] Next, each of the above slurries was applied to a positive electrode current collector and a negative electrode current collector, respectively, and dried to prepare a preliminary electrode. The negative and positive electrode slurries were applied onto Cu and Al foils, respectively, using the doctor blade method, and dried at 60°C for more than 12 hours using a vacuum. A 10 µm thick Cu foil and a 12 µm thick Al foil were used as the negative and positive electrode current collectors, respectively.

[0115] Next, a slurry for the solid electrolyte layer was prepared. The slurry was prepared by mixing solid electrolyte particles (Cl-added Li2S-P2S5 (Mitsui metal)) and a binder (polyacrylate (SX-A334, Zeon)) in a xylene solvent inside an argon-filled glove box. At this time, the weight ratio of the solid electrolyte to the binder was 98:1. The slurry was prepared by stirring four times for 3 minutes using a paste mixer. Subsequently, the slurry for the solid electrolyte layer was applied to the cathode surface and dried. The slurry for the solid electrolyte layer prepared using the doctor blade method was applied to the cathode surface prepared by the previous application and drying process, and dried under vacuum at 60°C for more than 12 hours. Next, a laminated structure was prepared by stacking the coated surface and the anode facing each other, and then a lamination process was performed to achieve interlayer bonding. At this time, the lamination process was performed under room temperature conditions and at a pressure of 400 MPa for about 10 minutes. The thickness of the solid electrolyte layer in the obtained electrode assembly was about 50 μm.

[0117] Example 4

[0118] The lamination process was performed in the same manner as in Example 3, except that the lamination process was performed at a pressure of 100 MPa under conditions of 120°C. The thickness of the solid electrolyte layer in the obtained electrode assembly was approximately 50 μm.

[0120] Comparative Example 1

[0121] A positive electrode slurry and a negative electrode slurry were prepared.

[0122] Graphite and NMC (LiNi) as active materials for the manufacture of cathode and anode slurries 0.7 Mn 0.15 Co 0.15O2 particles were used. Li2S-P2S5-LiCl (Mitsui metal) was used as the sulfide-based solid electrolyte. The cathode consisted of a mixture of graphite and solid electrolyte particles in a weight ratio of 80:20, and the anode consisted of a mixture of NMC and solid electrolyte particles in a weight ratio of 75:25. The experiment was conducted using a glove box filled with argon gas to avoid contamination from contact with air and moisture. A separate conductive material (Vapor Grown Carbon Fiber (VGCF)) and a binder (polyacrylate (SX-A334, Zeon)) were additionally added to the xylene solvent, and a slurry was prepared by rotating a paste mixer at 1,000 rpm for 5 minutes.

[0123] Next, each of the above slurries was applied to the positive current collector and the negative current collector, respectively, dried, and then a pressurization process was performed to prepare a preliminary electrode. The pressurization process was performed at room temperature for about 10 minutes, and a pressure of about 400 MPa was applied.

[0124] The cathode and anode slurries were coated onto Cu and Al foils, respectively, using the doctor blade method, and dried at 60°C for more than 12 hours using a vacuum. A 10 µm thick Cu foil and a 12 µm thick Al foil were used as the cathode and anode current collectors, respectively.

[0125] Next, a slurry for the solid electrolyte layer was prepared.

[0126] A slurry for a solid electrolyte layer was prepared by mixing solid electrolyte particles (Cl-added Li2S-P2S5 (Mitsui metal)) and a binder (polyacrylate (SX-A334, Zeon)) in a xylene solvent inside an argon-filled glove box. At this time, the weight ratio of the solid electrolyte to the binder was 98:1. The slurry was prepared by stirring four times for 3 minutes using a paste mixer.

[0127] Subsequently, the slurry for the solid electrolyte layer was divided into two parts, and using a doctor blade, a portion was applied to the surface of the cathode and the remainder to the surface of the anode. Afterward, the mixture was dried at 60°C for more than 12 hours using a vacuum, followed by a pressurization process. The pressurization process was performed at room temperature for approximately 3 minutes, and a pressure of approximately 400 MPa was applied.

[0128] Next, a laminated structure was prepared by stacking the coated surfaces facing each other, and then a lamination process was performed to bond the layers. At this time, the lamination process was performed for about 10 minutes at a pressure of 400 MPa and room temperature. The thickness of the solid electrolyte layer in the obtained electrode assembly was about 50 μm.

[0130] Comparative Example 2

[0131] The lamination process was performed in the same manner as Comparative Example 1, except that the lamination process was performed at 120°C at a pressure of 100 MPa. The thickness of the solid electrolyte layer in the obtained electrode assembly was about 50 μm.

[0133] Comparative Example 3

[0134] A positive electrode slurry and a negative electrode slurry were prepared.

[0135] Graphite and NMC (LiNi) as active materials for the manufacture of cathode and anode slurries 0.7 Mn 0.15 Co 0.15O2 particles were used. Li2S-P2S5-LiCl (Mitsui metal) was used as the sulfide-based solid electrolyte. The cathode consisted of a mixture of graphite and solid electrolyte particles in a weight ratio of 80:20, and the anode consisted of a mixture of NMC and solid electrolyte particles in a weight ratio of 75:25. The experiment was conducted using a glove box filled with argon gas to avoid contamination from contact with air and moisture. A separate conductive material (Vapor Grown Carbon Fiber (VGCF)) and a binder (polyacrylate (SX-A334, Zeon)) were additionally added to the xylene solvent, and a slurry was prepared by rotating a paste mixer at 1,000 rpm for 5 minutes.

[0136] Next, each of the above slurries was applied to the positive current collector and the negative current collector, respectively, dried, and then a pressurization process was performed to prepare a preliminary electrode. The pressurization process was performed at room temperature for about 10 minutes, and a pressure of about 400 MPa was applied.

[0137] The cathode and anode slurries were coated onto Cu and Al foils, respectively, using the doctor blade method, and dried at 60°C for more than 12 hours using a vacuum. A 10 µm thick Cu foil and a 12 µm thick Al foil were used as the cathode and anode current collectors, respectively.

[0138] Next, a slurry for the solid electrolyte layer was prepared.

[0139] A slurry for a solid electrolyte layer was prepared by mixing solid electrolyte particles (Cl-added Li2S-P2S5 (Mitsui metal)) and a binder (polyacrylate (SX-A334, Zeon)) in a xylene solvent inside an argon-filled glove box. At this time, the weight ratio of the solid electrolyte to the binder was 98:1. The slurry was prepared by stirring four times for 3 minutes using a paste mixer.

[0140] Subsequently, the slurry for the solid electrolyte layer was applied to the cathode surface using a doctor blade and dried at 60°C for more than 12 hours using a vacuum. Afterward, a rolling process was performed. The pressurization process was performed at room temperature for about 3 minutes, and a pressure of about 400 MPa was applied.

[0141] Next, a laminated structure was prepared by stacking the coated surface and the anode facing each other, and then a lamination process was performed to bond the layers. At this time, the lamination process was performed for about 10 minutes at a pressure of 400 MPa and room temperature. The thickness of the solid electrolyte layer in the obtained electrode assembly was about 50 μm.

[0143] Comparative Example 4

[0144] The lamination process was performed in the same manner as Comparative Example 1, except that the lamination process was performed at 120°C at a pressure of 100 MPa. The thickness of the solid electrolyte layer in the obtained electrode assembly was approximately 50 μm.

[0146] Evaluation experiment

[0147] Measurement of ion conductivity

[0148] Electrochemical impedance was measured at room temperature with an amplitude of 10 mV in a frequency range from 1 MHz to 0.1 Hz using an analysis device (VMP3, Bio logic science instrument), and ionic conductivity was calculated based on this.

[0149] Rct was calculated from the intersection point where the measured EIS Semi-Circle meets the real axis, and the ionic conductivity (δ [S / cm]) was calculated from the area and thickness of the sample using the formula below.

[0150] δ = L / Rct * A

[0151] δ Ion Conductivity [S / cm]

[0152] Rct measured resistance (Ω)

[0153] L Distance between entire houses

[0154] A sample cross-sectional area

[0155] The results are shown in Fig. 10. According to this, it was confirmed that the batteries of Examples 1 and 2 have superior ion conductivity characteristics compared to the batteries of Comparative Examples 1 and 2.

[0157] Verification of initial charge / discharge characteristics

[0158] Please check the experiment method below.

[0159] The initial charge-discharge characteristics of the batteries obtained in Example 2 and Comparative Example 2 were verified. The initial charge-discharge characteristics were verified by performing charge-discharge at room temperature with a rate capability of C / 10 in a voltage range of 3.8V to 2.0V.

[0160] The results are shown in Figure 11. According to this, it was confirmed that the battery of the example has excellent initial charge / discharge characteristics, with a higher relative capacity compared to the battery of the comparative example until a low voltage is reached, and a low overpotential is observed during charging and discharging in the battery of the example.

Claims

Claim 1 A method for manufacturing an electrode assembly comprising an anode, a cathode, and a solid electrolyte layer interposed between the anode and the cathode, wherein the anode, the solid electrolyte layer, and the cathode are each sequentially stacked in a non-pressurized state to form a stacked structure, and a lamination process is performed on the stacked structure to form an electrode assembly, wherein the lamination process is performed under heat and / or pressure conditions, and the method comprises: S210) a step of preparing anode and cathode slurries; S220) a step of preparing a non-pressurized preliminary anode and a non-pressurized preliminary cathode by applying the anode and cathode slurries to an anode current collector and a cathode current collector, respectively, and drying them; S230) a step of preparing a slurry for a solid electrolyte layer, applying it to the surface of the preliminary anode and the surface of the preliminary cathode, respectively, and drying it to form a non-pressurized solid electrolyte layer on the surface of the preliminary anode and the surface of the preliminary cathode, respectively. and S240) a step of manufacturing an electrode assembly by stacking and laminating a preliminary anode and a preliminary cathode having a solid electrolyte layer formed in a non-pressurized state, such that the solid electrolyte layers in a non-pressurized state face each other, wherein the anode, cathode, and solid electrolyte layer comprise a sulfide-based solid electrolyte. Claim 2 A method for manufacturing an electrode assembly for an all-solid-state battery according to claim 1, wherein the lamination process is performed under conditions of a pressure of 80 MPa to 120 MPa and a temperature of 100°C to 150°C. Claim 3 A method for manufacturing an electrode assembly for an all-solid-state battery according to claim 1, wherein the lamination process is performed under conditions of a pressure of 350 MPa to 450 MPa and room temperature. Claim 4 A method for manufacturing an electrode assembly for an all-solid-state battery according to claim 1, wherein the slurry for the solid electrolyte layer comprises a sulfide-based solid electrolyte and a solvent, and the solvent comprises an aromatic solvent or a non-polar solvent. Claim 5 A method for manufacturing an electrode assembly for an all-solid-state battery according to claim 1, wherein the positive electrode comprises a positive electrode active material and a solid electrolyte, and the solid electrolyte comprises a sulfide-based solid electrolyte. Claim 6 A method for manufacturing an electrode assembly for an all-solid-state battery according to claim 5, wherein the positive active material and the solid electrolyte have a weight ratio of 60% to 95% for the positive active material and 5% to 40% for the solid electrolyte. Claim 7 A method for manufacturing an electrode assembly for an all-solid-state battery according to claim 1, wherein the cathode comprises a cathode active material and a solid electrolyte, and the solid electrolyte comprises a sulfide-based solid electrolyte. Claim 8 A method for manufacturing an electrode assembly for an all-solid-state battery according to claim 7, wherein the negative electrode active material and the solid electrolyte have a weight ratio of 60-80% for the negative electrode active material and 20-40% for the solid electrolyte. Claim 9 A method for manufacturing an electrode assembly for an all-solid-state battery, wherein, in claim 1, the solid electrolyte layer further comprises a binder resin. Claim 10 An electrode assembly comprising a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, wherein the positive electrode, the negative electrode, and the solid electrolyte layer comprise a sulfide-based solid electrolyte and is manufactured by the method according to claim 1.

Citation Information

Patent Citations

  • Solid battery

    KR1020140074176A

  • A solid-state battery and preparation thereof

    KR1020170069065A

  • Method for producing all-solid-state battery, and all-solid-state battery

    KR1020150076103A